Optimizing Zakat Crowdfunding for Poverty Alleviation: A Case Study of LAZISNU DIY - Gustanto, Edo Segara (Unisia, 2025)
This study examines how zakat crowdfunding can be optimized as an instrument for poverty alleviation through a case study of LAZISNU Special Region of Yogyakarta. Grounded in the context of persistent poverty and the underutilization of Indonesia’s vast zakat potential, the research aims to analyze the role of digital crowdfunding in enhancing the effectiveness, transparency, and social impact of zakat management. Employing a qualitative case study approach, the study collects data through in-depth interviews with zakat managers, donors, and beneficiaries, supported by participant observation and document analysis, with data validity ensured through triangulation. The findings show that zakat crowdfunding implemented by LAZISNU DIY operates through multiple digital platforms and is characterized by high transparency, ease of access, and active donor participation. These features strengthen public trust and significantly increase donor engagement, particularly among digitally literate contributors. The study also finds that zakat crowdfunding supports a shift from consumptive assistance toward productive and empowerment-oriented programs, such as microenterprise support, entrepreneurial training, and educational assistance, which contribute to greater economic resilience among beneficiaries. However, challenges remain, including uneven digital literacy, technological infrastructure constraints, and the need for stronger regulatory and governance frameworks. Overall, the study concludes that zakat crowdfunding represents a meaningful innovation in Islamic social finance, with important implications for zakat institutions and policymakers seeking sustainable poverty alleviation through transparent, technology-driven, and empowerment-focused zakat management.